Pengaruh Faktor Lingkungan terhadap Kepatuhan Wajib Pajak (Studi pada Wajib Pajak Orang Pribadi yang Terdaftar di Kantor Pelayanan Pajak Pratama Singaraja) - Ketut Deita Candra Prayoga; I Nyoman Putra Yasa (Universitas Pendidikan Ganesha, 2020)
This study aims to examine social environmental factors / subjective norms within the framework theory of planned behavior consisting of aspects of gender, age, religiosity, level of education, and level of income towards the intention to behave obediently to individual taxpayers registered at the Pratama Singaraja Tax Office. This research uses a quantitative approach with survey research methods. The sampling technique is purposive sampling, with a total sample of 347. The data source is primary data by collecting data using a questionnaire distributed online via Google form. The data obtained were then analysis using multiple linear regression analysis and ANOVA test (1 lane) with the help of the SPSS program. The results of this study state that (1) Gender has a positive and significant effect on the intention to behave in tax compliance, (2) There is a significant difference between age and intention to behave in tax compliance, (3) Religiosity has a positive and significant effect on intention to behave in tax compliance, (4 ) The level of education has a positive and significant effect on the intention to behave in tax compliance, and (5) The level of income has a positive and significant effect on the intention to behave in tax.